Literature review on the development and trends of battery technology in Indonesia (2020–2025) - Ria Aprilianingsih; Uvi Desi Fatmawati; Achmad Darwin; Nahdya Aufa Hayla Anwar; Bayu Nuar Khadapi Hasibuan (International Enterprise Integration Association, 2026)
The worldwide shift toward low-carbon energy systems has intensified demand for advanced battery technologies, particularly in the context of electric vehicle (EV) proliferation. Despite Indonesia's strategic position as the world's largest nickel producer holding approximately 21% of global nickel reserves comprehensive scholarly synthesis that integrates material innovation, industrial policy, regulatory frameworks, recycling systems, and consumer adoption within a unified analytical framework remains absent from the existing literature. This gap motivates the present study, which employs a Systematic Literature Review (SLR) methodology drawing upon 26 peer-reviewed articles and reports published between 2020 and 2025, sourced from IEEE Xplore, ScienceDirect, SpringerLink, Scopus, and Google Scholar. Thematic content analysis was applied to classify findings across nine interconnected dimensions: battery material evolution, manufacturing investment, charging infrastructure, regulatory challenges, recycling systems, consumer behavior, environmental impact, SWOT analysis, and emerging technologies. The principal contribution of this study lies in constructing an integrated ecosystem mapping of Indonesia's battery industry a synthesis not previously offered in the literature revealing that while NMC and LFP lithium-ion technologies have been rapidly adopted and manufacturing capacity is projected to reach 140 GWh by 2030, critical structural weaknesses persist in domestic research capacity, regulatory harmonization, and circular economy implementation. Solid-state and sodium-ion batteries are identified as strategically significant future directions. These findings offer actionable guidance for policymakers, researchers, and industry stakeholders seeking to strengthen Indonesia's long-term competitiveness in the global battery supply chain.